Uzbek Portrait Art in the Second Half of the XX Century - Mahmudov Azizbek Odiljonovich (International Journal on Integrated Education, 2022)
The article provides information about the events of the historical past, works dedicated to historical figures living in the recent or distant past, portrait compositions, works of Uzbek portrait painters. You can find information about some of the works from the historical past in world literature.